Peningkatan Usaha Milky Pudding Dapurmaunyaa - Mustika Permata Dewi; Kriswanto Widiawan (Jurnal Titra, 2021)
Each product undergoes several steps in a product life cycle, namely introduction, growth, maturity, and decline. One of the SMEs in Kudus, Central Java named Dapurmaunyaa also underwent such product life cycle. The sales of Dapurmaunyaa’s milky pudding experienced continuous decline for three consecutive months. This research aimed to find the root cause of the decreasing sales numbers and its solution for future business development. Open interviews and questionnaire distribution were done to pinpoint customers’ reasons for not repurchasing the company’s products. The result of the research revealed boredom as the main factor of the sales numbers’ decrease. The best solution that could be done as an effort to increase sales numbers was by adding new flavor variations of the products sold.